2012
DOI: 10.1007/s12070-012-0578-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-pathological Profile and Management of Sino-nasal Masses: A Prospective Study

Abstract: The work was planned to study-the demographic profile of sino-nasal masses, the clinical and radiological findings of sino-nasal masses and the correlation of the clinical and radiological findings with the histopathology. The study was conducted on the patients having sino-nasal masses admitted in Department of ENT, SMS Hospital, Jaipur from August 2008 to July 2010. The study was designed to evaluate the demographic distribution, clinicopathological features, radiological finding of sino-nasal masses and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 10 publications
5
21
0
Order By: Relevance
“…Rawat et al documented 78.5% of sinonasal masses as nasal polyps. 13 Lathi et al found 71.4% of the sinonasal masses to be non neoplastic. 11 According to Gupta et al, the most common sinonasal mass encountered in his study was inflammatory polyp (69.56%) with antrochoanal polyp (42.39%) followed by ethmoidal polyp (17.39%) and angiomatous polyp (7.6%).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Rawat et al documented 78.5% of sinonasal masses as nasal polyps. 13 Lathi et al found 71.4% of the sinonasal masses to be non neoplastic. 11 According to Gupta et al, the most common sinonasal mass encountered in his study was inflammatory polyp (69.56%) with antrochoanal polyp (42.39%) followed by ethmoidal polyp (17.39%) and angiomatous polyp (7.6%).…”
mentioning
confidence: 98%
“…Rawat et al found 68.56% of histopathological diagnosis as non neoplastic, 22.72% as benign and 8.71% as malignant. 13 Gupta et al found 69.56% of sinonasal masses as non neoplastic. 12 Among benign neoplastic sinonasal masses, inverted papilloma in 6.52% cases and nasopharyngeal angiofibroma in 5.43% cases.…”
mentioning
confidence: 99%
“…In our study, most common type of sino-nasal polyp observed was ethmoidal polyp (63.4%) followed by antrochoanal polyp (33.4%), sphenoidal polyp (1.6%) and frontal polyp (1.6%) similar observations were made in study conducted by Rawat et al among the 142 sinonasal polyps where 65.5% were Ethmoidal polyp while 34.5% were antrochoanal polyp. 6 These observations shows that Ethmoidal polps are the most commonly observed sino-nasal polyps.…”
Section: Discussionmentioning
confidence: 82%
“…[4][5][6] The occurrence of nasal polyps was in our study was 25.6% which was comparable to other similar studies. [6][7][8] Chavan et al showed the most common benign sinonasal mass as the nasal polyp. 9 On examination, the mass was pale, glistening grape-like, insensitive to probing and did not bleed on touch.…”
Section: Discussionmentioning
confidence: 99%